Related multiplicity, as in Al-Durr Al-Masun by Al-Sam'in Al-Halabi (d. 756 AH) (College of Basic Education Research Journal, 2025)
Linguistic studies were untamed and were only agreed upon by  skilled grammarians and masters of science among  interpreters and interpreters of  Holy Qur’an. Since then, meaning and parsing have appeared as an inseparable duality, one inseparable from the other. However, they stipulated  presence and validity of meaning for parsing, so they had (parsing is a branch of meaning). Research, “Multiple attachments to (if) in Al-Durr Al-Masun written by Al-Sameen Al-Halabi (d. 754 AH).”  stopped at  multiplicity of  related word (then) in  Holy Qur’an and left its connection with one related thing. Connection between  meaning and  parsing was a close one, and accordingly,  first basis is  validity of  parsing. This multiplicity is in  possibility of a connection, as it indicates  greatness of  explanation of  Holy Qur’an and its miracle, as  meaning is shown in sura. Different in one structure, and all of this revolves around  meaning and understanding  context of  noble verses. Research was divided into two sections: the first, dealing with attachment to two related things, and this topic is also divided into attachment to a verb or noun and attachment to two verbs, Second topic: attachment to more than two related things, and in analyzing texts, We mention  words of Al-Samin Al-Halabi first after mentioning  noble verse.
Keywords: Attachment; possibility; meaning; parsing; face